Sexual Dysfunction and Hyperprolactinemia in Male Psychotic Inpatients: A Cross-Sectional Study - Erik Johnsen; Rune Kroken; Else-Marie Løberg; Eirik Kjelby; Hugo A. Jørgensen (Advances in Urology)
Introduction. Sexual dysfunction (SD) and hyperprolactinemia are frequently reported in patients with psychotic disorders and have the potential for severe complications but investigations in males are particularly scarce. The primary aims were to determine the prevalence of SD and hyperprolactinemia in male patients and to investigate whether associations exist between SD and prolactin levels. Methods. Cross-sectional data were obtained at discharge from the hospital or 6 weeks after admittance for patients acutely admitted for psychosis and treated with a second-generation antipsychotic drug. Results. Half the patients reported diminished sexual desire and more than a third reported erectile and ejaculatory dysfunctions with no differences among the drugs. More than half the sample was hyperprolactinemic. No association was found between prolactin levels and SD. Conclusion. High rates of SD and hyperprolactinemia were found in male patients and should be a treatment target. SD and hyperprolactinemia were not correlated.